Prospective Study on Circulating MicroRNAs and Risk of Myocardial Infarction - Zampetaki, Anna; Willeit, Peter; Tilling, Lindsey; Drozdov, Ignat; Prokopi, Marianna; Renard, Jean-Marie; Mayr, Agnes; Weger, Siegfried; Schett, Georg; Shah, Ajay; Boulanger, Chantal M; Willeit, Johann; et al. (My University, 2012)
This study sought to explore the association between baseline levels of microRNAs (miRNAs) (1995) and incident myocardial infarction (1995 to 2005) in the Bruneck cohort and determine their cellular origin.
Keywords: Biomarker; Endothelium; MicroRNA; Myocardial infarction; Platelets